El final del bandoler: aproximació a la literatura de patíbul de la Corona d'Aragó. - LLINARES PLANELLS, ALEJANDRO (Scripta, 2017)
During the modern era, numerous cord folders related to banditry were printed in the territories of the Crown of Aragon. A relevant part of these popular fiction tales is the end that the main characters of these stories usually suffer: being hanged in the gallows. This paper focuses on a little-known topic so far, such as public executions in literary texts. In these pages, I'll discuss the punitive ritual suffered by the criminal when he was going to be executed: forms of execution; torture; and the social and cultural intentionality theses chapbooks had. Furthermore, judicial documents will be compared with chapbooks in order to show that there could be a transfer of information between law institutions and the autors of these popular poems..